The Present State of Existential Interventions Within Palliative Care - Terao, Takeshi; Satoh, Moriaki (Frontiers in Psychiatry, 2022)
Existential psychotherapy is rooted in the European tradition of existential philosophy. Existential philosophers include Husserl and Heidegger, who were German, and Camus, Sartre, de Beauvoir, and Merleau-Ponty, who were French. Their works contain existentially ultimate themes such as death, freedom, meaninglessness, and isolation. Based on their knowledge of existential philosophy, Binswanger, Frankl, and Boss developed the earlier existential psychotherapies such as Dasein-analysis and Logotherapy, while May, Laing, and Yalom started later existential psychotherapies in the British and American culture. Recent articles about existential psychotherapy revealed that existential psychotherapy has been mainly used for patients with advanced cancer and/or terminal care (palliative care), during the last two decades. Focusing on patients with advanced cancer and/or terminal care, we found nine types of existential psychotherapies: Meaning-Centered Group Psychotherapy (MCGP), Individual Meaning-Centered Psychotherapy (IMCP), Meaning-Making intervention (MMi), Meaning of Life Intervention, Managing Cancer and Living Meaningfully (CALM), Hope Intervention, Cognitive and Existential Intervention, Dignity Therapy, and Life-Review Interviews, from 19 relevant randomized controlled trials. All deal with death, meaninglessness, and isolation, except freedom. Particularly, MCGP, IMCP, MMi, Meaning of Life intervention, and CALM emphasize finding and/or making meaning in the individual’s life. The effects on existential or spiritual well-being were confirmed in MCGP, IMCP, Meaning of Life intervention, and Life-Review intervention although the number of studies were very few. In the other interventions, there were heterogenous findings and again the number of studies was very small. Further studies are required to investigate the effects of existential psychotherapy on patients with advanced cancer.